2022
DOI: 10.3389/fcell.2022.909557
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte-mediated epigenomic instability in human T-ALL cells is cytotoxic and phenocopied by epigenetic-modifying drugs

Abstract: The world’s population with obesity is reaching pandemic levels. If current trends continue, it is predicted that there will be 1.5 billion people with obesity by 2030. This projection is alarming due to the association of obesity with numerous diseases including cancer, with recent studies demonstrating a positive association with acute myeloid leukemia (AML) and B cell acute lymphoblastic leukemia (B-ALL). Interestingly, several epidemiological studies suggest the converse relationship may exist in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…299 However, another study has indicated that obesity negatively affects T-ALL in mice models by inducing their apoptosis through epigenetic modification (histone H3 acetylation and methylation), which is inhibited by H3K27 demethylase inhibitor GSK-J4 and the pan-HDAC inhibitor vorinostat. 300 Notably, fasting does not affect AML initiation and progression. Details of fasting and dietary interventions in different cancers have been discussed elsewhere.…”
Section: Obesity and Allmentioning
confidence: 99%
See 1 more Smart Citation
“…299 However, another study has indicated that obesity negatively affects T-ALL in mice models by inducing their apoptosis through epigenetic modification (histone H3 acetylation and methylation), which is inhibited by H3K27 demethylase inhibitor GSK-J4 and the pan-HDAC inhibitor vorinostat. 300 Notably, fasting does not affect AML initiation and progression. Details of fasting and dietary interventions in different cancers have been discussed elsewhere.…”
Section: Obesity and Allmentioning
confidence: 99%
“…Furthermore, fasting alone robustly inhibits the initiation of ALL (B‐ALL and T‐ALL) and reverses their progression in mice and human xenograft models by upregulating LEPR and its downstream signaling through the protein PR/SET domain 1 (PRDM1) and insulin growth factor‐1 binding protein B1 (IGFB1), but decreasing the high circulating and BM leptin and IGF‐1 level 299 . However, another study has indicated that obesity negatively affects T‐ALL in mice models by inducing their apoptosis through epigenetic modification (histone H3 acetylation and methylation), which is inhibited by H3K27 demethylase inhibitor GSK‐J4 and the pan‐HDAC inhibitor vorinostat 300 . Notably, fasting does not affect AML initiation and progression.…”
Section: Obesity and Different Leukemiamentioning
confidence: 99%
“…1a). GSK-J4 is a small-molecule inhibitor functions on H3K27 histone demethylase JMJD3/UTX to suppress enzyme activity 29,30 . Subsequently, quantify immunofluorescence staining results also proved this phenomenon again (Figs.…”
Section: Emodin Inhibits the Expression Of Jmjd3 In Interstitial Cyst...mentioning
confidence: 99%